2019
DOI: 10.3847/2041-8213/ab12ed
|View full text |Cite
|
Sign up to set email alerts
|

TESS Delivers Its First Earth-sized Planet and a Warm Sub-Neptune*

Abstract: The future of exoplanet science is bright, as TESS once again demonstrates with the discovery of its longest-period confirmed planet to date. We hereby present HD 21749b (TOI 186.01), a sub-Neptune in a 36-day orbit around a bright (V = 8.1) nearby (16 pc) K4.5 dwarf. TESS measures HD21749b to be 2.61 +0.17 −0.16 R ⊕ , and combined archival and follow-up precision radial velocity data put the mass of the planet at 22.7 +2.2 −1.9 M ⊕ . HD 21749b contributes to the TESS Level 1 Science Requirement of * This pape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 53 publications
9
55
0
Order By: Relevance
“…As expected, most of these confirmed exoplanet-hosting stars are in the thin disc (e.g. Jones et al 2018;Wang et al 2018;Dragomir et al 2019;Huber et al 2019). Esposito et al (2018) reported the existence of a hot Neptune orbiting an inactive G7 dwarf star, TOI 118, which we classify as a kinematic thick disc star.…”
Section: The Chemo-kinematics Of the Tess Objects Of Interestsupporting
confidence: 59%
“…As expected, most of these confirmed exoplanet-hosting stars are in the thin disc (e.g. Jones et al 2018;Wang et al 2018;Dragomir et al 2019;Huber et al 2019). Esposito et al (2018) reported the existence of a hot Neptune orbiting an inactive G7 dwarf star, TOI 118, which we classify as a kinematic thick disc star.…”
Section: The Chemo-kinematics Of the Tess Objects Of Interestsupporting
confidence: 59%
“…We considered stars with P thick /P thin > 10 to be in the thick disk while stars in between (0.1 < P thick /P thin < 10) are ambiguous to judge. Up to now, TESS has detected five planet host stars located in the in-between region: TOI 118 (Esposito et al 2019), TOI 144 (Huang et al 2018b), TOI 172 (Rodriguez et al 2019), TOI 186 (Trifonov et al 2019;Dragomir et al 2019) andTOI 197 (Huber et al 2019). Table 4 lists their relative probabilities and none of them show clear-cut thick-disk probability.…”
Section: Thick-disk Characteristicsmentioning
confidence: 99%
“…For the first time in human history, it is possible to find and characterize nearby rocky and potentially hab-et al 2007;Dressing & Charbonneau 2015) − systems that are especially amenable to spectroscopic observation due to their high transit frequency, low star-toplanet brightness contrasts, prolonged main sequence lifetimes, and abundance in both the solar neighborhood and the projected Transiting Exoplanet Survey Satellite (TESS) sample (Henry et al 2006;Barclay et al 2018). Indeed, TESS has already found small and Earthsized planets transiting cool stars (e.g., Vanderspek et al 2019;Dragomir et al 2019). Upcoming characterization efforts by the James Webb Space Telescope, groundbased 30-meter extremely large telescopes, and direct imaging missions will likely attempt to detect habitability indicators (e.g., N 2 , H 2 O v ) and/or biosignatures (O 2 , O 3 , CH 4 , N 2 O, CO 2 ; Sagan et al 1993) on these K-and M-dwarf systems.…”
Section: Introductionmentioning
confidence: 99%